PELATIHAN KREDIT USAHA RAKYAT (KUR) SEBAGAI SUMBER PEMBIAYAAN UKM - Rasyid, Rosmita; Christianto ATS, Einstein (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2024)
Small and medium-sized enterprises (SMEs) can tackle various issues like creating jobs, strengthening local economies, and seizing opportunities from global business trends. These efforts can also boost community well-being, raise incomes, stimulate regional growth, and ultimately contribute to national economic progress. However, SMEs often face challenges such as financial constraints, business risks, and the significant threat of failure. Since new SMEs usually rely on personal funds for funding, their investment potential is limited. Thankfully, there are different financing options available to bridge this gap, especially to support innovative activities. For instance, a batik handicraft business in Jambi was selected for a Community Services (PKM) project aiming to enhance their understanding of business capital sources for product innovation. This project utilized Zoom for training sessions. Topics covered included capitalization basics, business credit, and credit requirements. The project successfully increased the partners' awareness of People's Business Credit (KUR) and resolved business issues, enabling them to boost their capital for product development. Furthermore, the outcomes of the PKM project were disseminated through national journals and intellectual property rights protection.